Thoughts on the eidetic variation theory - Rosales, Alberto (Estudios de Filosofía, 2008)
The Husserlian method of eidetic variation is generally interpreted on the basis of his brief expositions in the lesson Phenomenological Psychology (= PF, 1925) and in Experience and Judgment (= EyJ, 1936), which do not reveal the foundations and limits of this method. In order to shed light on them, we refrain from commenting on these versions of the method itself, which has already been done by several authors, and we consider in a first section Husserl’s theory (= H) on essences, their classes and the corresponding methods of knowing them. On this basis, the second section deepens the understanding of eidetic variation by formulating some critical considerations about it and its limits. [Fragment]